Protected Areas in Forest Conservation: Challenges and Opportunities - Dimitrakopoulos, Panayiotis; Jones, Nikoleta (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Forest ecosystems are important habitats for a vast number of species worldwide. These ecosystems are degrading faster than they are regenerating, due to the increased demand for natural resources. In order to protect these ecosystems, the designation of Protected Areas (PAs) has become the primary policy tool for forest conservation. The articles included in this book explore challenges and opportunities within forest PAs, focusing on four main themes. The first theme refers to current initiatives in forest management across the world, reflecting the efforts of several organizations in halting deforestation. Major challenges are also identified, reflecting the declining rates of forest coverage across the world. A second theme refers to policy planning processes withing existing governance frameworks focusing, in particular, on the level of engagement of local stakeholders. A third theme of the book refers to social equity and how the impacts of forest PAs are distributed among different users. A final theme in the SI refers to potential solutions in order to halt the loss of biodiversity within forest ecosystems. Several directions are proposed by the authors that can be useful for policy makers and practitioners, especially in the context of the 30 by 30 targets.